Genetic diversity and relationships in jute (Corchorus spp.) revealed by SSR markers (Bangladesh Journal of Botany, 2010)
Characterization of sixteen jute genotypes, from Corchorus olitorius L. and Corchorus capsularis L. using jute specific SSR marker attained a high polymorphism value of 92.20%. A total of 171 different alleles were amplified by 27 primer pairs with a mean of 6.33 ± 2.04 alleles per locus. The genetic diversity was also relatively high (0.81 ± 0.06). The Un-weighted Pair-group Method with Arithmetic averages (UPGMA) cluster analysis of the 16 jute genotypes produced a dendogram, which was in concordance with known information. The study reinforces the utility of SSR primers for providing useful and high levels of markers for individual plant genotypes even with a narrow genetic base. Key words: Jute; Genetic diversity; SSR; Genotypes; Polymorphism DOI: 10.3329/bjb.v38i2.5140 Bangladesh J. Bot. 38(2): 153-161, 2009 (December)